A Comparative Assessment of Emerging Solvents and Adsorbents for Mitigating CO2 Emissions From the Industrial Sector by Using Molecular Modeling Tools - Bahamon, Daniel; Alkhatib, Ismail I. I.; Alkhatib, Nour; Builes, Santiago; Sinnokrot, Mutasem; Vega, Lourdes F. (Frontiers in Energy Research, 2020)
Some specific examples are presented showing the possibilities offered by molecular modelling tools to obtain relevant data at process conditions while also gaining molecular insights on the techniques used for CO2 capture and separation. Two different technologies, absorption with amine-based systems and adsorption on porous materials, were explored, using the molecular-based equation of state, soft-SAFT, and Grand Canonical Monte Carlo simulations, respectively. The aqueous monoethanolamine (MEA) system was used as the benchmark for absorption and compared to the performance of eight alternative amine-based systems, while sixteen adsorbents belonging to different families (zeolites, Metal Organic Frameworks, silicas and activated carbons), bare or functionalized with alkylamines, were investigated for the separation of CO2 by adsorption. In addition to obtaining molecular information on the CO2 capture process, the models were further used to examine the CO2 capture performance in terms of cyclic working capacity and energy index as key performance indicators, allowing the identification of promising systems that can improve the current ones to be further evaluated for separation in non-power industries. Results show that for the same total amine mass concentration, non-aqueous amine solvents possess a 5–10% reduction in cyclic working capacity, with a 10-30% decrease in the energy index compared to their aqueous counterparts, due to lower heat of vaporization and sensible heat. It has also been obtained that M-MOF-74 and zeolites NaX and NaY structures offer the best results for adsorption in TSA processes. Some adsorbent structures achieved similar values of energy requirement to the ones obtained for alternative amine-based systems (2-2.5 MJ∙kgCO2-1), although the disadvantage of the TSA process versus absorption should be taken into account. These results confirm the reliability of the molecular modelling approach as an attractive and valuable screening tool for CO2 capture and separation processes.